(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the impact of word-of-mouth in social media on consumers’ decision-making for purchasing a product. One hundred and fifty-four responses from Eastern Mediterranean University, Turkish Cypriot, and Turkish customers were used in the questionnaire. T-test and ANOVA were conducted to examine the relationship between word-of-mouth and its determinants. The results of independent T-test show that both males and females have a significant difference in their consideration of offline word-of-mouth messages for commercial activities. Results also show that Females rely more on word-of-mouth than males for commercial purposes. The results of ANOVA explain that younger respondents were more eager to use online networks for commercial purposes than their older counterparts. There was no significant difference between people’s job status in their use of social media for commercial purposes, online and offline word-of-mouth reliance.